Production of Emulsion Paint Using Locally Available Materials. - Turyarugayo, Emmanuel (Kabale University, 2024)
Many toxic chemicals such as titanium dioxide are used in the manufacture of chemical paints. These chemicals are not only expensive to purchase and use but also hazardous to human health and release harmful compounds to our environment after exposure to the chemical paints made on the interior and exterior surfaces where the painting is done. However, these chemical elements or compounds can be replaced with safer locally available materials. This study aims to come up with an emulsion paint product using locally available materials from our environment in a small-scale enterprise. Using experimental methods, an emulsion paint product was prepared in the laboratory using water, lime, clay, milk, rice flour, and lampblack as raw materials. The different physical and chemical tests were carried out on the emulsion paint product such as application test, drying time, durability or weather resistance test, adhesion test, and pH test. Some of the physicochemical properties fell within the required Uganda Standard or East African Community Standards for chemical paints. The study therefore recommended that small-scale entrepreneurs and local people should begin producing emulsion paints from water, lime, clay, milk, rice flour, and lampblack since the materials are readily available in our environment, cheap, and friendly to our environment.